2019
DOI: 10.1108/prt-12-2017-0105
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of novel pigments derived from Red Lake C

Abstract: Purpose The purpose of this study is to prepare new pigments derived from Red Lake C (RLC) to be applied in the inks industry and to identify their chemical nature, as well as their physical properties. Design/methodology/approach A number of pigments that could be applied in special printing were prepared via the reactions of RLC with appropriate Ni(II) and Zn(II) salts in aqueous and ethanolic solutions. The obtained pigments were prepared as solid compounds and characterized using different instrumental a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The results of viscosity shown in Table 4 clarified that the viscosity of the printing ink containing the blue pigment is higher than that of the commercial one. The viscosity of the prepared ink containing the blue pigments was 62 s, whereas the viscosity of the commercial ink was 45 s. This proves that the integration of the blue pigment in the ink formulation increases the viscosity; therefore, the prepared ink could be diluted, and hence multiplication of the ink quantity could be occurred, leading to decreasing the price of the final product (Abdelmaksoud, 2019). Also, the gloss of the printing ink containing the blue pigment was the best.…”
Section: Coating Applicationsmentioning
confidence: 83%
See 1 more Smart Citation
“…The results of viscosity shown in Table 4 clarified that the viscosity of the printing ink containing the blue pigment is higher than that of the commercial one. The viscosity of the prepared ink containing the blue pigments was 62 s, whereas the viscosity of the commercial ink was 45 s. This proves that the integration of the blue pigment in the ink formulation increases the viscosity; therefore, the prepared ink could be diluted, and hence multiplication of the ink quantity could be occurred, leading to decreasing the price of the final product (Abdelmaksoud, 2019). Also, the gloss of the printing ink containing the blue pigment was the best.…”
Section: Coating Applicationsmentioning
confidence: 83%
“…The flexographic printer can print hundreds of personalized labels in a short period of time via transferring ink onto a substrate such as a film, paper and/or cardboard. Flexographic printing is popular because of its speed, cost-effectiveness and low environmental impact (Abdelmaksoud, 2019; Wang et al , 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous work (Abdelmaksoud et al , 2019), we have reported two new pigments obtained during the reaction of RLC with Ni(II) and Zn(II) salts. Herein and in continuation of our research study, new pigments were prepared by reaction of LR with Mn(II) and Co(II) ions via an efficient simple route.…”
Section: Introductionmentioning
confidence: 99%